Digoxigenin activates autophagy in hepatocellular carcinoma cells by regulating the PI3K/AKT/mTOR pathway - Mengqing Ma; Rui Hu; Qi Huang; Jing Li; Minling Lv; Jialing Sun; Xin Zhong; Jinyu Yi; Lanfen Peng; Wenxing Feng; Wenfeng Ma; Zhiyi Han; et al. (Cancer Cell International)
Abstract Hepatocellular carcinoma (HCC) is recognized as a highly malignant tumor. Targeted combination immunotherapy, the initially approved regimen, is compromised by adverse side effects and low response rates during clinical treatment. Traditional Chinese medicine and its derived natural compounds, known for their anticancer effects, offer advantages of low toxicity and cost. In this study, we performed high-throughput phenotypic screening in vitro to identify promising anti-HCC drugs. Among 1,444 bioactive compounds, digoxigenin (DIG) was found to significantly impede HCC cell progression. We validated DIG’s therapeutic effects through assays such as cell counting by CCK8, lactate dehydrogenase, and colony formation. Analyses including transmission electron microscopy, western blotting, and immunofluorescence demonstrated that DIG inhibits HCC cell proliferation via autophagy. Network pharmacology and molecular docking studies suggest that DIG targets the PI3K/AKT/mTOR signaling pathway. Comparative treatments of Hep3B and Huh7 cells with DIG or mTOR inhibitors revealed similar inhibitory impacts, indicating that DIG induces autophagy by inhibiting the PI3K/AKT/mTOR pathway. In vivo studies confirmed that DIG halts the growth of subcutaneous xenograft tumors. In conclusion, DIG represents a potential HCC treatment by modulating the PI3K/AKT/mTOR pathway to induce autophagy. This research, via phenotypic screening, accelerates drug discovery and the development of novel therapies targeting the underlying mechanisms of liver cancer.